Standardisation and customisation of healthcare facility design in nation building: sharing Malaysian experience - Mohd Nawawi, Norwina (2006)
Standard and customized designs had been the Malaysian phenomena in public facility building programme including healthcare. The practice was initiated prior to Malaysia‟s independence till today to meet the local and global (WHO) needs towards a healthy nation. The paper thus intends to share this rare experience, being part of the British Commonwealth and of multi-ethnicity and multi religion population, the pros and the cons of the approach in the quest of nation building towards sustainable future. Over provision or utilization of standards dampened creativity and innovation of any design towards purported holistic function of a healthcare facility. The paper dwells briefly on the historically framework of the physical development that leads to the decision in the use of standard or customized design, and bring about subsequent development in various Malaysian development plans towards a developed nation. Case studies on the various level of care, especially hospitals, will be use to illustrate the pros and cons on the design development of its healthcare facilities, its available resources and perceived aspirations throughout the 49 years of independence. The paper will highlight the Malaysia‟s approach to provide comprehensive healthcare infrastructure to the country with the intention that good and bad lessons learnt throughout the process can benefit other developing nation similar to Malaysia. The study will be conducted through literature review of published and unpublished publication for secondary data, and through observation and structured interviews with relevant government personnel for primary data. The significance of the study will hope to highlight the limits both standardization and customization of design can be carried out through pragmatic planning without losing the focus of what the health facility is for i.e. uplifting the standards of health in the country physically, mentally and spiritually.